Methodological challenges and solution strategies during implementation of a midwife-led multicenter randomized controlled trial (RCT) in maternity hospitals - Sabine Striebich; Elke Mattern; Theresa Oganowski; Rainhild Schäfers; Gertrud Ayerle (BMC medical research methodology, 2021)
Randomized controlled trials (RCTs), especially multicentric, with complex interventions are methodically challenging. Careful planning under everyday conditions in compliance with the relevant international quality standard (Good Clinical Practice [GCP] guideline) is crucial. Specific challenges exist for RCTs conducted in delivery rooms due to various factors that cannot be planned beforehand. Few published RCTs report challenges and problems in implementing complex interventions in maternity wards. In Germany as well as in other countries, midwives and obstetricians have frequently little experience as investigators in clinical trials.